2018
DOI: 10.1177/0004563218778701
|View full text |Cite
|
Sign up to set email alerts
|

Does the mass of sample loaded affect faecal haemoglobin concentration using the faecal immunochemical test?

Abstract: Background Quantitative faecal immunochemical tests (FIT) for haemoglobin are being used for colorectal cancer (CRC) screening for asymptomatic populations and are being indicated as a suitable test to rule out CRC in symptomatic populations. Faecal samples are typically collected by patients using a probe attached to the cap of a device which is inserted into a collection device into the preservative buffer, passing through a collar to remove excess sample: this process has potential for pre-analytical error.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…Some brands of FIT promote collection of feces from multiple sites and, although this was not shown to alter diagnostic accuracy compared with sampling from just one site (19), instruction for multi-site sampling might reduce the risk of under-sampling. Our results, and that of a published in vitro study that loaded up to 74 mg on to the collection device probe (10), confirm that over-sampling does not adversely affect diagnostic accuracy and clinical outcomes, provided that at least 10 mg is collected and inserted into the device.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some brands of FIT promote collection of feces from multiple sites and, although this was not shown to alter diagnostic accuracy compared with sampling from just one site (19), instruction for multi-site sampling might reduce the risk of under-sampling. Our results, and that of a published in vitro study that loaded up to 74 mg on to the collection device probe (10), confirm that over-sampling does not adversely affect diagnostic accuracy and clinical outcomes, provided that at least 10 mg is collected and inserted into the device.…”
Section: Discussionsupporting
confidence: 79%
“…However, factors related to the collection itself may also influence the diagnostic accuracy and subsequent clinical performance, such as quantity of feces collected in the device. Results from previous studies on the effect of the addition of different quantities of fecal samples are inconsistent, with one study showing that the addition of feces to Hb-spiked buffer changed the measured f-Hb (9), whereas another study showed that varying the quantity of Hb-spiked feces collected in the FIT devices did not significantly change f-Hb (10).…”
Section: Introductionmentioning
confidence: 92%
“…The iO (CV range 0.9–15.5%) uses the OC-Sampling Bottle 3 which previous work has shown has a well-designed internal collar to remove excess faeces; this study showed the mass of faeces loaded on to the probe did not affect the concentration of Hb captured by the device. 14 The QuikRead go (CV range 2.6–17.5%) has a similar design with a tight fitting collar to remove excess faeces. The Cube has a collar but it is not as tight as the other two devices which could lead to increased variation in the amount of faeces in the buffer.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we demonstrated that artificially overloading of samples didn’t impact the faecal haemoglobin concentration (f-Hb) significantly. 3 In this study we further investigated with patient samples whether there was an association between the total mass of the collection device and corresponding f-Hb. We also investigated if faecal material that remained adhered to the dimple(s) of the device affected f-Hb.…”
mentioning
confidence: 99%
“…This is consistent with our previous findings that loading of excess faeces around the dimple(s) of the collection device and higher up had no significant impact on the f-Hb. 3…”
mentioning
confidence: 99%